Steam balloon concept for lifting rockets to launch altitude. (May 2019) - Janhunen, P.; Toivanen, P.; Ruosteenoja, K.
ABSTRACT: Launching orbital and suborbital rockets from a high altitude is beneficial because of e.g. nozzle optimisation and reduced drag. Aircraft and gas balloons have been used for the purpose. Here we present a concept where a balloon is filled with pure water vapour on ground so that it rises to the launch altitude. The system resembles a gas balloon because no onboard energy source is carried, and no hard objects fall down. We simulate the ascent behaviour of the balloon. In the baseline simulation, we consider a 10 tonne rocket lifted to an altitude of 18 km.We model the trajectory of the balloon by taking into account steam adiabatic cooling, surface cooling, water condensation and balloon aerodynamic drag. The required steam mass proves to be only 1.4 times the mass of the rocket stage, and the ascent time is around 10 minutes. For small payloads, surface cooling increases the relative amount of steam needed, unless insulation is applied to the balloon skin. The ground-filled steam balloon seems to be an attractive and sustainable method of lifting payloads such as rockets into high altitude.